O pensamento multifacetado de Aurino Ribeiro Filho (1947-2015) - Dourado, Márcio Caetano da Silva (2022)
The present work aims to understand the many-faceted aspect of Professor Aurino Ribeiro Filho’s thought (1947-2015) through the analysis of his academic trajectory and his performance as the head of the Physics Institute at the Federal University of Bahia (IFUFBA). As a black scientist and intellectual, with a solid formation in the country and abroad, Aurino Ribeiro Filho was an outstanding presence in the development of high-level research carried out at the Federal University of Bahia (UFBA). As a student he stood out in both theoretical and experimental fields of Physics, later becoming one of the main coordinators who helped to consolidate the Post-Graduate Program at the IFUFBA. Always seeking to find new standards or surpassing those already established, Professor Aurino Ribeiro Filho was also the main coordinator of precious dialogues between different areas and researchers at the University. Thus, through publications and open seminars, including to the wider public, he spread a many-faceted vision of knowledge, which marked his entire career